PENERAPAN KEDISIPLINAN TERHADAP KINERJA KARYAWAN (Studi pada PT. PDAM Surya Sembada Surabaya) (Jurnal Bisnis Indonesia, 2022)
PDAM Surya Sembada Surabaya City is a drinking water company owned by the regional government of Surabaya. The interesting thing to study at PDAM Surya Sembada Surabaya is related to the discipline of its employees. Handling customer complaints is usually resolved quickly if there are no problems in the field. This shows that the employee's performance is quite good and can be said to be disciplined in receiving, sorting and selecting, and resolving customer complaints. In this research, the type of research used is quantitative and associative research. This type of research is field research. Data collection techniques are through observation, interviews, questionnaires and literature study. For data processing analysis techniques, namely linear regression analysis.The results of the study indicate that the discipline of PDAM Surya Sembada Surabaya employees can be said to be quite good. This can be seen from the disciplinary indicators whose questions were answered by respondents and stated that the discipline of PDAM Surya Sembada Surabaya received a fairly good response from employees. However, employee discipline must still be considered in order to prevent employee negligence at work.  DOI : https://doi.org/10.33005/jbi.v13i1.3084